Incidence of leaf rot disease in relation to root (wilt) in young coconut palms and fungi in lamina and petiole lesions - N. Srinivasan (International Coconut Community, 2004)
Coconut leaf rot in association with root (wilt) is widespread in southern districts of Kerala, India. The disease complex has spread to northern districts of the state and also adjacent districts in Tamil Nadu. Where as the root (wilt) is a systemic infection (due to phytoplasma) the leaf rot is a foliar syndrome due to fungi (Colletotrichum gloeosporioides, Exserohilum rostratum, Fusarium spp.). Occurrence of leaf rot has been related to the incidence of root (wilt) and its appearance in young palms remained a matter of contention as to which disease precedes the other. Leaf rot lesions do occur on leaf petiole/mid-vein/mid-rib even as the disease lesions are known to be common on lamina (spindles). Investigations brought out that in majority of leaf rot affected young palms (2-5 years old) the flaccidity symptom of root (wilt) could be also discerned. In lesser number of affected palms, the other symptoms of root (wilt), yellowing and marginal necrosis, were also visible. As such, in 88.5% of leaf rot affected young palms one or the other symptom of root (wilt) has been recorded irrespective of season. C. gloeosporioides, E. rostratum and other fungi were found both in lamina and petiole lesions in different months. C. gloeosporioides was detected from petiole and lamina tissues in all the months, followed by E. rostratum, Fusarium spp. etc. C. gloeosporioides was isolated from these parts in more numbers and consistently during January-December. E. rostratum appeared erratically. Aggressiveness of C. gloeosporioides during months of wet season was confirmed. Fusarium spp. was isolated predominantly from these parts in dry months (January-May). Knowledge on occurrence of leaf rot in young palms in relation to root (wilt) and dynamics of leaf rot pathogens in leaf parts among months/seasons of year (in inoculums build-up, spread and dissemination) are important in the context of integrated management of root (wilt)-leaf rot complex.